CORRELATIONS BETWEEN SALIVARY CORTISOL LEVELS AND PERIODONTAL DISEASE. REVIEW - Bogdan-Constantin Vasiliu; Stefan-Alexandru Trufanda; Cornelia Teodorescu; Silvia Teslaru; Ioana-Andreea Sioustis; Ionut Luchian; Alexandra-Maria Martu; Diana-Cristala N; Irina-Georgeta Sufaru; Ioana Rudnic; Liliana Pasarin; Sorina-Mihaela Solomon; et al. (Romanian Dental Association for Education, 2021)
The term "periodontal disease" is properly assigned to gingivitis and periodontitis. Generally, gingivitis is a condition of the epithelial and connective tissues located in the immediate vicinity and subcolletal area of the tooth. From the etiopathogenic point of view, gingivitis is the result of the immediate exposure of the aggressive microbial factor through bacterial plaque, physical, chemical, thermal or other traumas such as irradiation, smoking. Cortisol induces metabolic processes antagonistic to insulin, especially during times of hunger and sustained stress. Cortisol influences the immune and inflammatory defense system. Selected articles involving psychosocial stress, anxiety, and depression directly related to periodontal disease reached the following conclusions: psychological stress highlighted by increased salivary cortisol levels influences periodontal disease by exacerbating it and increasing loss of attachment. at probing, potentiation of probing bleeding; the increased index of anxiety is correlated with the increased level of salivary cortisol and chronic periodontitis